Synthesis of modified cyclic and acyclic dextrins and comparison of their complexation ability - Tuza, Kata; Jicsinszky, László; Sohajda, Tamás; Puskás, István; Fenyvesi, Éva (Beilstein Journal of Organic Chemistry, 2014)
We compared the complex forming ability of α-, β- and γ-cyclodextrins (α-CD, β-CD and γ-CD) with their open ring analogs. In addition to the native cyclodextrins also modified cyclodextrins and the corresponding maltooligomers, functionalized with neutral 2-hydroxypropyl moieties, were synthesized. A new synthetic route was worked out via bromination, benzylation, deacetylation and debenzylation to obtain the 2-hydroxypropyl maltooligomer counterparts. The complexation properties of non-modified and modified cyclic and acyclic dextrins were studied and compared by photon correlation spectroscopy (PCS) and capillary electrophoresis (CE) using model guest compounds. In some cases cyclodextrins and their open-ring analogs (acyclodextrins) show similar complexation abilities, while with other guests considerably different behavior was observed depending on the molecular dimensions and chemical characteristics of the guests. This was explained by the enhanced flexibility of the non-closed rings. Even the signs of enantiorecognition were observed for the chloropheniramine/hydroxypropyl maltohexaose system. Further studies are planned to help the deeper understanding of the interactions.
Keywords: acyclodextrin; cyclodextrin; ibuprofen; maltodextrin; maltoheptaose; maltohexaose; maltooctaose

(untitled) - Noltemeyer, M.; Saenger, W. (Nature, 1976)

(untitled) - Fanta, G. F.; Shogren, R. L.; Salch, J. H. (Carbohydr. Polym., 1999)

(untitled) - Lay Ma, U. V.; Floros, J. D.; Ziegler, G. R. (Carbohydr. Polym., 2011)

(untitled) - Gabelica, V.; Galic, N.; De Pauw, E. (J. Am. Soc. Mass Spectrom., 2002)

(untitled) - Komiyama, M.; Hirai, H.; Kobayashi, K. (Makromol. Chem., Rapid Commun., 1986)

(untitled) - Bettinetti, G. P.; Mura, P.; Melani, F.; Rillosi, M.; Giordano, F. (J. Inclusion Phenom. Mol. Recognit. Chem., 1996)

(untitled) - Sicoli, G.; Jiang, Z.; Jicsinszky, L.; Schurig, V. (Angew. Chem., 2005)

(untitled) - Sicoli, G.; Pertici, F.; Jiang, Z.; Jicsinszky, L.; Schurig, V. (Chirality, 2007)

(untitled) - Smith, N. W.; Evans, M. B. (J. Pharm. Biomed. Anal., 1994)

(untitled) - Chankvetadze, B.; Endresz, G.; Blaschke, G. (Electrophoresis, 1994)

(untitled) - Chankvetadze, B.; Lindner, W.; Scriba, G. K. E. (Anal. Chem., 2004)

(untitled) - Garnero, C.; Zoppi, A.; Genovese, D.; Longhi, M. (Carbohydr. Res., 2010)

(untitled) - Rundlett, K. L.; Armstrong, D. W. (J. Chromatogr., A, 1996)

Methods in Carbohydrate Chemistry - Lemieux, R. U. (Tetra-O-acetyl-a-D-glucopyranosyl Bromide, 1963)

(untitled) - Lindberg, B. (Acta Chem. Scand., 1949)

Methods in Carbohydrate Chemistry - Thompson, A.; Wolfrom, M. L. (Deacetylation, 1963)

(untitled) - Jicsinszky, L.; Iványi, R. (Carbohydr. Polym., 2001)